Association of mineral composition of neonatal intravenous feeding solutions and metabolic bone disease of prematurity. Issue 4 (April 1989) - MacMahon, P; Blair, M E; Treweeke, P; Kovar, I Z
Abstract : To assess the effects of increasing the mineral content of parenteral nutrition solutions on the biochemical and radiological indicators of metabolic bone disease of prematurity 27 neonates who required parenteral nutrition were sequentially allocated to receive either a standard solution (group 1) or one with an increased mineral content (group 2). The 13 patients in group 1 received 0.68 mmol/kg/day of calcium and 0.61 mmol/kg/day of phosphorus, and the 14 in group 2 received 1.25 and 1.20 mmol/kg/day, respectively. The two groups did not differ significantly in the severity of their illness measured by birth weight, gestational age, duration of parenteral nutrition or ventilation, or the amount of supplementary oxygen required. In patients in group 2 the median plasma phosphate concentration was higher, the plasma alkaline phosphatase activity was lower, and there was less radiological evidence of rickets. There were no complications caused by excess calcium and phosphorus, and the rate of growth was similar in both groups. We conclude that an increased mineral content in parenteral nutrition solutions reduces the severity of metabolic bone disease in sick infants who require this form of nutrition.